Big Data, machine learning and challenges of high dimensionality in financial administration - Yaohao, Peng (2019)
Tese (doutorado)—Universidade de Brasília, Faculdade de Economia, Administração e Contabilidade e Gestão Pública, Programa de Pós-Graduação em Administração, 2019.